(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
In the current paper, the relationship between caste, gender, and political representation in India is critically examined through a combination of the visual and the political science approach. It transcends a purely data-driven approach in its attempt to comprehend how the existing social orders, institutional structures and cultural practices dictate who gains access to political power. Within the framework of intersectionality, the research points to the fact that persons being at the cross-section of marginalized caste identities and gender face both additional and structurally entrenched obstacles to participation and leadership. Although affirmative action policies, such as reservations, have enhanced descriptive representation in different political institutions, it has not always been accompanied by substantive empowerment or policy impact. The paper also highlights the drawbacks of depending only on quantitative visualization in the sense that it should engage more analytically with the issue of power relations, agency, and democratic inclusion. The study highlights the importance of more inclusive, intersectional, and institutionally responsive methodologies by locating the empirical patterns in the larger socio-political contexts. Finally, it demands a reconsideration of the nature of representation in the context of equity, voice, and meaningful representation to enhance democratic legitimacy in India.